Vascular Access for Long-Term Hemodialysis/Hemodiafiltration Patients. Issue 10 (November 2015) - Yokota, Narushi; Nagai, Kojiro; Okada, Daigo; Muromiya, Yasuto; Suenaga, Takehiro; Ueda, Yuka; Kawahara, Kana; Kanayama, Hiro-omi; Minakuchi, Jun; Tsuchida, Kenji
Purpose: We investigated the characteristics of patients who received long-term hemodialysis/hemodiafiltration (HD/HDF) treatment for over 30 years at our group of hospitals and type of vascular access (VA) used. Subjects and methods: As of August 2014, 950 patients were receiving HD/HDF treatment at one of our hospitals. Of those, we investigated 41 (4.3%) undergoing long-term treatment in regard to their characteristics and VA type. The items subjected to analysis were sex, primary illness, age at time of dialysis initiation, present age, duration (years) of HD/HDF, type of arteriovenous fistula (AVF) and arteriovenous graft (AVG), history of surgery and AVF persistence rate. Results: The subjects consisted of 22 men and 19 women, and their mean HD/HDF duration was 33.4 ± 2.8 years. For primary illness, the majority (n = 31) had chronic glomerulonephritis. The age at time of dialysis initiation was 31.7 ± 7.76 years and present age was 64.5 ± 7.65 years. They had received 3.8 VA surgeries. For present VA type, 23 patients (56.0%) had an AVF and 13 (31.7%) an AVG, while 4 AVF patients (9.7%) had a history of AVG use. One patient (2.4%) had a superficialized artery. The mean HD/HDF duration of the 13 AVG patients was 7 years and the longest was 18 years. AVF persistence rate estimated by the Kaplan-Meier method was 75% at 30 years after dialysis initiation. Conclusions: The present results suggest that the ratio of patients with AVG increased with prolonged HD/HDF treatment. AVG has a higher probability of complications and lower patency as compared to AVF, thus careful management is needed. On the other hand, AVG contributes more to a good long prognosis, as it offers efficient dialysis. In cases of vascular deterioration due to long-term hemodialysis, it is inevitable to change from AVF to AVG, thus the ratio of AVG patients is expected to increase in cases of long-term HD/HDF.